Acceptability of medical immobilization: Results from a pilot international survey. Issue 5 (27th April 2022) - Townsend, Janice A.; Peng, Jin; McDaniel, Jodee C.; Casamassimo, Paul S.
Abstract: Background: Controversy exists on the acceptability of medical immobilization (MI). Aim: To identify regulations, professional conventions, and opinions on the acceptability of MI and to identify practice patterns through a pilot study of members of the International Association of Paediatric Dentistry (IAPD) and their colleagues. Design: A 22‐item questionnaire was developed and electronically distributed to 1191 members of the IAPD. Results: Responses were received from 182 dentists in 45 countries. The majority (74.9%) of respondents use MI, and 29.1% use an immobilization device. MI with an immobilization device was reported as professionally acceptable (58.1%) and permitted by medicolegal regulations (70.8%) in their countries of practice. Dentists rated acceptability of MI higher than they perceived parents would overall and perceived MI to be more acceptable by parents for emergency situations and for children with special healthcare needs but 19.8% of respondents found it totally unacceptable in all scenarios. Use and opinions of acceptability varied by geographical location with respondents from North America being more accepting of MI. Most dentists felt that the use of an immobilization device could lead to lasting psychological trauma (72.3%) and violation of the rights of the child (55.4%) but that it improves access to care (58.5%). Conclusion: The acceptability of MI remains an area of controversy for paediatric dentists internationally.